A Systematic Literature Review of Students' Spatial Visual Ability in Geometry Transformation Based on Student Achievement - Khaebibah, Jelita Fuji; Hartono, Wahyu; Nopriana, Tri (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2026)
Visual–spatial ability represents a critical cognitive component in mathematics learning, particularly in geometric transformations, including rotation, translation, reflection, and dilation. Although previous studies have emphasized the importance of this ability, limited research has examined visual–spatial ability based on students’ academic achievement levels (high, medium, and low). This study presents a systematic literature review (SLR) of 24 empirical articles published between 2020 and 2025 to examine the relationship between visual–spatial ability and learning success in geometric transformations across different achievement groups. The study selection followed the PRISMA 2020 guidelines and utilized two primary databases, namely Crossref and Google Scholar. Thematic analysis was employed to identify patterns of effective instructional strategies and variations in students’ responses across achievement levels. The findings indicate that high-achieving students generally demonstrate stronger spatial capabilities that support abstract understanding of geometric concepts, whereas low-achieving students benefit more from contextualized and concrete visual approaches. These results highlight the importance of implementing differentiated pedagogical strategies that align instructional design with students’ achievement profiles in order to optimize learning outcomes in geometric transformation topics.